(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This research examines the language development of a three-year-old child through Lev Vygotsky’s socio-cultural theory. Utilizing journals and observations, the researcher explores the child’s acquisition of some language constructs within a social and cultural context. The study emphasizes the vital role of social interactions, including conversations with parents and peers, in shaping the child’s linguistic progress. The analysis spans several months, highlighting a few linguistic constructs and their correlation with everyday situations and play interactions. This research contributes to the understanding of child language development by emphasizing the significance of socio-cultural factors. The study underscores the practical application of Vygotsky’s socio-cultural theory and offers insights for English as a Foreign Language (EFL) teachers, educators, and caregivers. Ultimately, the findings highlight the importance of creating a nurturing socio-cultural environment to foster a child’s linguistic development.